Al-Attas on Justice: Toward Islamic Patronage and Economic Sustainability - Nur Majdina; Firda Inayah; Taufiq Ramadhan (Universitas Darussalam Gontor, 2026)
This paper investigates the concept of justice within the intellectual framework of Syed Muhammad Naquib al-Attas. It assesses its implications for shaping an Islamic patronage paradigm oriented toward economic sustainability. Motivated by the need to address social and economic distortions produced by contemporary patronage practices and ethical biases, the study employs a qualitative research design that integrates a philosophical approach with a descriptive-analytical method. The study finds that justice, understood as ‘a condition in which things are in their proper places’, extends beyond socio-legal structures to encompass ontological and epistemological order. This conception provides a substantive foundation for the practice of Islamic patronage, which surpasses transactional dynamics between patron and client and instead constitutes a social mechanism rooted in the Islamic worldview, particularly the values of piety (taqwā), excellence (iḥsān), and trustworthiness (amānah). These justice-based principles, as demonstrated, bear significant implications for ethical governance, community empowerment, and sustainable economic development through the cultivation of economic ecosystems, social entrepreneurship, policy advocacy, and institutional strengthening.